2020
DOI: 10.1029/2020gl087970
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Buried Lake Drainage on the Antarctic Ice Sheet

Abstract: Between 1992 and 2017, the Antarctic Ice Sheet (AIS) lost ice equivalent to 7.6 ± 3.9 mm of sea level rise. AIS mass loss is mitigated by ice shelves that provide a buttress by regulating ice flow from tributary glaciers. However, ice‐shelf stability is threatened by meltwater ponding, which may initiate, or reactivate preexisting, fractures, currently poorly understood processes. Here, through ground penetrating radar (GPR) analysis over a buried lake in the grounding zone of an East Antarctic ice shelf, we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…6 (2020)). It makes sense that these features are co-located because they both require similar climatic conditions of high melt and high accumulation to exist (Koenig et al, 2014;Munneke et al, 2014;Dunmire et al, 2020). The buried lakes detected in this study are likely located at shallower depths than the firn aquifers because they can be detected in S1 imagery, unlike most firn aquifers which are too deep to be detected directly in S1 imagery.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…6 (2020)). It makes sense that these features are co-located because they both require similar climatic conditions of high melt and high accumulation to exist (Koenig et al, 2014;Munneke et al, 2014;Dunmire et al, 2020). The buried lakes detected in this study are likely located at shallower depths than the firn aquifers because they can be detected in S1 imagery, unlike most firn aquifers which are too deep to be detected directly in S1 imagery.…”
mentioning
confidence: 81%
“…Previous studies have generally assumed that buried lakes on the GrIS develop when a surface lake partially freezes through and then gets buried by snowfall, insulating any remaining liquid water under the surface (Koenig et al, 2015;Schröder et al, 2020). Modelling efforts have confirmed that this process is sufficient to allow liquid water to exist under the ice surface throughout the winter on both the Greenland and Antarctic ice sheets (Law et al, 2020;Dunmire et al, 2020;Lampkin et al, 2020). In SW Greenland, most of the detected buried lakes had some surface meltwater within their bounds during the previous melt season (Fig.…”
Section: Buried Lake Formation Processesmentioning
confidence: 94%
See 1 more Smart Citation
“…The model atmosphere is initialised on 1 January 1979 using ERA-Interim. RACMO2.3p2 includes a 100-layer firn model that calculates percolation, refreezing, and run-off of liquid water (Ettema et al, 2010). The output of this internal firn model is not used in this study as the model is physically identical to IMAU-FDM described below, but the latter runs at a higher vertical resolution (100 layers in RACMO2 vs. 3000 layers in IMAU-FDM).…”
Section: Regional Atmospheric Climate Model Racmo23mentioning
confidence: 99%
“…In this study, AP firn characteristics including potential PFA formation are assessed using two snow models: the Institute for Marine and Atmospheric Research Utrecht Firn Densification Model (IMAU-FDM; Ligtenberg et al, 2011) and SNOWPACK (Bartelt and Lehning, 2002). The models are forced by realistic atmospheric and surface conditions from the Regional Atmospheric Climate MOdel (RACMO2.3p2) for the period 1979-2016, which has been extensively evaluated with observational datasets, as have previous versions (Van Wessem et al, 2015Wessem et al, , 2016Wessem et al, , 2018, and includes a snow model that is physically identical to IMAU-FDM (Ettema et al, 2010;Ligtenberg et al, 2011). This combination of models accurately simulates PFA locations in Greenland (Forster et al, 2013;Steger et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%